Eco-Drainage System Towards Sustainable Urban Environment - Shamsuddin, Nurfisah (Universiti Teknologi PETRONAS, 2010)
Sustainable urban drainage is a concept that includes long-term environmental and social factors in the planning and design of drainage systems. The function is to manage the stormwaters in developments that replicate the natural drainage. The project is to develop the drainage system to support an aquatic life that promotes balance ecosystems and at the same time examines the best infiltration devices based on the condition at the residential area in Bandar Seri Iskandar, Perak. Infiltration is the process by which water on the ground surface enters the soil. Infiltration rate in soil science is a measure of the rate at which soil is able to absorb rainfall or irrigation. Based from the studies explained that the infiltration device was suitable to be implemented at the site area of Sri Iskandar. The purpose of the infiltration device was to take off runoff water from development and allows it to percolate into the ground. It reduced the volume of water that has to be disposed of through sewers and then recharge of groundwater to maintain water level in local watercourses. From the result, there were some improvement in the water quality elements such as turbidity, pH value, COD, BOD5, DO, Ammonia Nitrogen and Total Phosphorus. For the turbidity the percentage of removal was 11.63%, COD reduce to 39.29%, BOD reduce to 25.16%, Ammonia Nitrogen reduce to 9.68%o and Total Phosphorus reduce to 9.86%. This project was still under development phase where there will be some requirements and aspects that need to be addressed of.